Applications of Machine Learning 2021 (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Applications of Machine Learning 2021 held on 1-5 August 2021, San Diego, California, United States.
Keywords: Machine learning.; elektronické knihy; electronic books